Surviving the Crisis and Austerity: The Coping Strategies of Portuguese Households - Frade, Catarina (2015)
Uma versão revista deste artigo foi publicada em: Frade, Catarina; Coelho, Lina (2015), "Surviving the Crisis and Austerity: The Coping Strategies of Portuguese Households", Indiana Journal of Global Legal Studies, 22, 2, 631-664. doi:10.2979/indjglolegstu.22.2.631.